Occupational Therapy Using CBT to Improve Work Productivity in Schizophrenia: A Case Study - Artha Nisa Thohiroh Triyantari; Nur Arsyi, Reza; Muhammad Luthfi; Ayleen Alicia K; Hermito Gideon; Zulfa Khoirunisah; Putri Dirgantara; Purnama Betty R. Sitorus (Jurnal Fisioterapi Terapan Indonesia, 2024)
Schizophrenia is a chronic mental disorder that often impairs an individual's social and occupational functioning, including productivity-related activities. Patients with schizophrenia frequently face challenges in maintaining employment or running an independent business due to cognitive and emotional disturbances affecting their adaptive skills. This single-case study integrates Cognitive Behavioral Therapy (CBT) into occupational therapy to enhance productivity in a schizophrenia patient through an entrepreneurial activity—independently opening a coffee shop. The study subject is a 50-year-old male diagnosed with schizophrenia undergoing psychosocial rehabilitation at RSJ Dr. Soeharto Heerdjan. The CBT-based intervention was designed to develop adaptive thinking patterns and occupational skills through modeling, role-playing, homework assignments, and educational experiences in a small business setting. Evaluation was conducted using the Comprehensive Occupational Therapy Evaluation Scale (COTE) and direct observation throughout the program. The results showed improvements in endurance, categorization of tools and equipment, financial management, and adherence to standard operating procedures (SOP) in customer service. Additionally, the intervention led to enhanced initiative, time management, and self-control, which are key challenges in the productivity of individuals with schizophrenia. The novelty of this study lies in the application of CBT within occupational therapy as an entrepreneurial rehabilitation approach for schizophrenia patients, an area rarely explored in conventional occupational therapy interventions. Findings suggest that occupational therapy not only supports daily living skills but can also serve as an economic empowerment tool, fostering financial independence among individuals with mental health disorders. This approach has the potential for further development in productivity-based psychosocial rehabilitation programs in mental health institutions.